1978
DOI: 10.1002/1520-6807(197807)15:3<327::aid-pits2310150303>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The Bender Gestalt Test: A review of reported research with school-age subjects, 1966-1977

Abstract: The past 11 years of published research investigating the use of the Bender Gestalt Test with school‐age children are reviewed. Seen as a psychometric instrument, scored according to standardized procedures, this recent work does not conclusively support the use of the test for prediction of school achievement. Nor does it offer any substantial support for individual diagnosis of neurological impairment or emotional disturbance. Test scores from group and individual administration appear equivalent. Deprived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0
4

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 97 publications
0
4
0
4
Order By: Relevance
“…Kitay (1972) suggested that the BG can be used as a part of most assessments of adults and children over 5 years of age because of the information it provides about a person's perceptual-motor functioning, expressive style, and possible maladjustment. However, out of 225 studies reviewed by Buckley (1978), only 4 concluded that the BG is a valid instrument for diagnosing academic achievement.…”
mentioning
confidence: 99%
“…Kitay (1972) suggested that the BG can be used as a part of most assessments of adults and children over 5 years of age because of the information it provides about a person's perceptual-motor functioning, expressive style, and possible maladjustment. However, out of 225 studies reviewed by Buckley (1978), only 4 concluded that the BG is a valid instrument for diagnosing academic achievement.…”
mentioning
confidence: 99%
“…Sua relevância é confirmada pelo número de pesquisas no âmbito nacional e estrangeiro, assim como pela sua freqüência de uso clínico. Escolheu-se o sistema de Koppitz, por ser o mais citado, e o B-SPG por ser não apenas o único método de correção com parâmetros brasileiros, como de autores nacionais (Buckley, 1978;Noronha & cols., 2002).…”
Section: Discussionunclassified
“…O teste de Bender consta dentre os instrumentos mais utilizados na avaliação psicológica, como pode ser verificado em revisões realizadas nos países estrangeiros (Buckley, 1978;Lubin & Sands, 1992;Sangster, Rogers & Searight, 1993). Também no plano nacional há indicativos de que o teste é bastante conhecido e utilizado tanto por profissionais como por estudantes de psicologia (Noronha, 2002;Noronha et al, 2002).…”
unclassified
“…Buckley (1978) concluiu que faltam evidên-cias de validade para muitos dos usos para os quais é indicado, como por exemplo, para a predição de rendimento escolar ou problemas neurológicos. O valor dos critérios de correção utilizados foi questionado por autores como Shapiro e Partenio (1995), Taylor, Kauffman e Partenio (1984), por exemplo, com a afirmação de que há limitações na interpretação da pontuação obtida, com conseqüentes problemas para sua utilização no diagnóstico neuropsicológico, bem como na identificação de aspectos desenvolvimentais.…”
unclassified